Wordplay and World-Play: The Minima Visibilia in The Construction of Linguistic Sciences - Emad Abd Elkareem Alqadumi (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
This paper aims to illustrate, by using a single sentence as the focus of the study, the inseparability of wordplay and worldplay. It intends to illustrate how playing with a sentence like